Data mining and statistics methods for advanced training course quality measurement: Case study - Maxim Galchenko; Alexander Gushchinsky; Waldemar Izdebski; Jacek Skudlarski (Foundations of Management, 2014)
Advanced training courses in the energetics field is a very important part of human reliability growth. In the words of S.E. Magid, chief of Technical Educational systems in Energy Technologies, UNESCO department: 'The number of forced outages due to failures of equipment on the power stations -30 %. The share of operational personnel fault in these infringements makes considerable size (to 15%). As a whole in the Russian Open Society 'United Power Systems' the infringements percentage because of the personnel from infringements total makes 2%. At the same time, on power stations this quantity makes 18%. In power supply systems of Siberia the relative quantity of infringements because of the personnel reaches 50%.' [1].
Keywords: 650; advanced training course; educational data mining; statistics methods